Análise de redes sociais de colaboração dos programas de pós-graduação no campo da Geoquímica - Gomes, Verônica de Souza (2023)
The characterization of a postgraduate program with a level of excellence goes through an evaluation process with different criteria to demonstrate its performance and its consonance with institutional planning. In Brazil, postgraduate programs are the locus of knowledge production and the process of building science. In this sense, analyzing a program based on scientific production and collaboration practices can reveal the directions that are occurring in science and guide the decisions of policy makers. Thus, the objective of this research is to analyze the social network of scientific collaboration of Postgraduate Programs in the area of Geosciences related to the field of Geochemistry in Brazil, based on the scientific production of permanent professors from the four-year period (2017-2020), as well as how to map the profile of programs. In this way, the research presents a review of the concepts coined by the Social Studies of Science. The research starts from an exploratory phase, with a quali-quantitative approach, which includes the search for evidence regarding production processes and collaboration in the construction of scientific knowledge. The bibliometric approach and Social Network Analysis are used to analyze the structure of scientific communication and the practices of social actors in the field of Geochemistry. The units of analysis comprise seven Postgraduate Programs – Postgraduate Program in Geosciences at the Federal University of Rio Grande do Sul, Postgraduate Program in Geology at the University of Brasília, Postgraduate Program in Geosciences (Geochemistry and Geotectonics) at the University of São Paulo, Postgraduate Program in Geosciences (Geochemistry) at the Federal University of Fluminense, Postgraduate Program in Geology and Geochemistry at the Federal University of Pará, Postgraduate Program in Geosciences at the Federal University of Pernambuco , and the Postgraduate Program in Geochemistry: Petroleum and Environment at the Federal University of Bahia. The main sources of information used in the research were the Sucupira Platform and the Lattes Platform. From the results it was possible to map and profile the seven Programs, obtaining a set of indicators of scientific production and teachers based on data from the Lattes Curriculum. Through Social Network Analysis it was possible to identify the actors and structures that strengthen the field of Geochemistry in Brazil. So, the group of actors analyzed in the programs was 220, through the production of 1,567 journal articles indexed in the Web of Science. The actors established collaborative relationships of an intra-interinstitutional nature. In addition to being one of the oldest programs, the Postgraduate Program in Geosciences at the Federal University of Rio Grande do Sul was the most significant in terms of scientific production, number of professors, productivity grants, degrees and projects. In the co-authorship network, the central actor of the network was “Elton Luiz Dantas”, professor of the Postgraduate Program in Geology at the University of Brasília. It is believed that the results presented contribute to the understanding of relationships in the field of Geochemistry and provide support for new studies. In this way, Governments, funding agencies and academic institutions can use Social Network Analysis data to make informed decisions about research investments and inter-institutional collaborations.